Obesity and sudden cardiac death in the young: Clinical and pathological insights from a large national registry. (March 2018) - Finocchiaro, Gherardo; Papadakis, Michael; Dhutia, Harshil; Cole, Della; Behr, Elijah R; Tome, Maite; Sharma, Sanjay; Sheppard, Mary N
Aims: Obesity is an increasing public health problem and a risk factor for cardiovascular diseases. The aim of the study was to determine the main features and aetiologies in a large cohort of sudden cardiac deaths that occurred in obese subjects. Methods: Between 1994 and 2014, 3684 consecutive cases of unexpected sudden cardiac death were referred to our cardiac pathology centre. This study was confined to young individuals (age ≤ 35 years) for whom information about body mass index was available and consisted of 1033 cases. Results: Two-hundred and twelve individuals (20%) were obese. In obese sudden cardiac death victims the main post-mortem findings were: normal heart (sudden arrhythmic death syndrome) ( n = 108; 50%), unexplained left ventricular hypertrophy ( n = 25; 12%) and critical coronary artery disease ( n = 25; 12%). Less common were hypertrophic cardiomyopathy ( n = 4; 2%) and arrhythmogenic right ventricular cardiomyopathy ( n = 4;2%). When compared with non-obese sudden cardiac death victims, sudden arrhythmic death syndrome was less common (50% vs. 60%, P < 0.01), whereas left ventricular hypertrophy and critical coronary artery disease were more frequent (12% vs. 2%, P < 0.001 and 12% vs. 3%, P < 0.001, respectively). The prevalence of critical and non-critical coronary artery disease was significantly higher in obese individuals (23% vs. 10% in non-obese individuals, P < 0.001). Conclusions: Various conditions underlie sudden cardiac death in obesity, with a prevalence of sudden arrhythmic death syndrome, left ventricular hypertrophy and coronary artery disease. The degree of left ventricular hypertrophy measured by heart weight is excessive even after correction for body size. Almost one in four young obese sudden death patients show some degree of coronary artery disease, underscoring the need for primary prevention in this particular subgroup.